2008
DOI: 10.1631/jzus.b0820002
|View full text |Cite
|
Sign up to set email alerts
|

Tannins from Canarium album with potent antioxidant activity

Abstract: Abstract:The contents of total phenolics and extractable condensed tannins in the leaves, twigs and stem bark of Canarium album were determined. The structural heterogeneity of condensed tannins from stem bark was characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and nuclear magnetic resonance (NMR) analyses. The results show the predominance of signals representative of procyanidins and prodelphinidins. In addition, epicatechin and epigallocatechin po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 23 publications
(22 reference statements)
1
54
0
2
Order By: Relevance
“…Radical scavenging activity was performed by using DPPH method (Zhang and Lin, 2008). The percentage of DPPH binding capacity of each pigmented extracts was calculated based on the formula:…”
Section: Determination Of Dpph Scavenging Capacitymentioning
confidence: 99%
“…Radical scavenging activity was performed by using DPPH method (Zhang and Lin, 2008). The percentage of DPPH binding capacity of each pigmented extracts was calculated based on the formula:…”
Section: Determination Of Dpph Scavenging Capacitymentioning
confidence: 99%
“…Therefore, new interest has been developed to search natural and safe antioxidative agents from natural sources. Among various naturally occurring substances, polysaccharides prove to be one of the useful candidates in search for effective, non-toxic substances with antioxidant activity (Liu et al, 1997;Zhang et al, 2003;Peterszegi et al, 2003;Zhang and Lin, 2008). Previous studies indicated that the bioactivities of polysaccharides can be affected by many factors including chemical components, molecular weight, structure, conformation, even the extraction and isolation methods (Leung et al, 2006;Zhang et al, 2007;Tseng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados obtenidos por el método del DPPH (figura 1) indican que el EAVT mostró un valor IC 50 mayor (IC 50 de 1,12 μg/mL) al estándar (IC 50 1,72 μg/mL) para inhibir el radical DPPH. Dicha capacidad antioxidante se atribuiría al alto contenido de fenoles totales que presenta, esto de acuerdo con estudios previos que indican una relación directa entre actividad antioxidante y contenido de fenoles totales en hierbas, vegetales y frutos (18) , y esta a su vez con el contenido de taninos y su eficiencia antirradical (19,20) . De acuerdo con la clasificación de Gomes de Melo y col. (21) , el EAVT muestra una buena actividad antioxidante, y resultados similares han sido reportados en otros estudios referentes a los extractos de vainas de tara (4,22) .…”
Section: Discussionunclassified